2021
DOI: 10.1177/08943184211031595
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Disorders in Military Veterans: An Evaluation with the Roy Adaptation Model

Abstract: The purpose of this paper was to evaluate a role for the Roy adaptation model (RAM) for the nursing care of military veterans with alcohol use disorder. Parse’s criteria were used to critique the RAM. The RAM’s humanistic philosophy emphasizes the ability to develop new coping skills and adapt to complex environments. The framework can define physical, emotional, and social responses to stressors faced by veterans. The RAM could guide new research and practice initiatives that optimize the health of military v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Relevant examples have been published about Newman's theory of health as expanding consciousness 40 and Roy's adaptation model. 41 When Stec 40 used the health as expanding consciousness framework to investigate nursing students' clinical reasoning approaches and interactions with patients, she found that students could only gather valuable information from patients after they established a trusting and transformative relationship with them. This study illustrated how a theory could guide students to optimize nurse-patient interactions by respecting others' perspectives.…”
Section: Nursing Theoriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Relevant examples have been published about Newman's theory of health as expanding consciousness 40 and Roy's adaptation model. 41 When Stec 40 used the health as expanding consciousness framework to investigate nursing students' clinical reasoning approaches and interactions with patients, she found that students could only gather valuable information from patients after they established a trusting and transformative relationship with them. This study illustrated how a theory could guide students to optimize nurse-patient interactions by respecting others' perspectives.…”
Section: Nursing Theoriesmentioning
confidence: 99%
“…This study illustrated how a theory could guide students to optimize nurse-patient interactions by respecting others' perspectives. In another example illustrating the importance of understanding different points of view, Hallihan et al41 used Roy's adaptation model to examine risk factors for alcohol use disorders in military veterans, finding that this population may require unique prevention and treatment plans. These examples illustrate how educators can use nursing theories as a clinically relevant schema for teaching students about symbolism and critical thinking.…”
Section: Using Philosophy To Design Critical Thinking Assignments For...mentioning
confidence: 99%
See 2 more Smart Citations